Photo's with text on the back by Antonia Fontanillas. Depicted photo shows: F.l.t.r.: Fontanillas Borrás, Torres Planells, C. and A. Carrera from Zaragazo, Cristalina from Gerona and A. Fontanillas Borrás
Photo's with text on the back by Antonia Fontanillas. Depicted photo shows: F.l.t.r.: Fontanillas Borrás, Torres Planells, C. and A. Carrera from Zaragazo, Cristalina from Gerona and A. Fontanillas Borrás.